Building Academic Culture Through Islamic Values: The Role of Independent Curriculum in Schools - Kilau Syamsiah; Budi Haryanto (Institut Agama Islam An-Nawawi Purworejo, 2024)
The independent curriculum is implemented in order to improve the quality and welfare of education in Indonesia. The independent curriculum includes three types of learning, namely intracurricular, co-curricular, and extracurricular. The application of an independent curriculum in learning is a crucial contribution in shaping an academic culture rooted in Islamic values. This study aims to determine the extent of the implementation of the independent curriculum in schools and its implications for the formation of Islamic values-based school academic culture. The method used is qualitative with a multicase study format. Data collection through observation, interview, and documentation techniques. The research location is in two institutions, namely SMA Al Fattah Sidoarjo and MAN Sidoarjo. The subjects of the study were principals, curriculum waka, educators, and students. Data analysis using domain analysis. Test the validity of the data using source and method triangulation types. The results showed that the implementation of the independent curriculum at SMA Al Fattah Sidoarjo and MAN Sidoarjo has changed the academic culture by providing freedom in curriculum preparation and integrating Islamic values. This change can be seen in several aspects ranging from the formation of academic culture, the cultivation of Islamic values, more collaborative forms of teaching and learning both the methods and learning media used, the psychological and social impact of students, and the participation of stakeholders who are very influential in the student learning process. The Merdeka Curriculum has had a positive impact in shaping the school's academic culture based on Islamic values by strengthening the school's identity and student character while helping to form highly competitive individuals based on strong Islamic values.